2010
DOI: 10.2214/ajr.09.3171
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Sonography for Small Hepatocellular Carcinoma Discovered by CT or MRI: Factors Affecting Sonographic Detection

Abstract: The overall detection rate for small (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
82
1
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(87 citation statements)
references
References 22 publications
1
82
1
3
Order By: Relevance
“…Although computed tomography (CT) and magnetic resonance imaging (MRI) are popular, US is still the most common modality for the initial investigation of the liver worldwide. Normally, the liver can be detected satisfactorily using US except some parts of the subphrenic region [4,5]. Previous studies have found that a tumor located in the subphrenic region is not easy to be detected and it may lead to missed diagnosis [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although computed tomography (CT) and magnetic resonance imaging (MRI) are popular, US is still the most common modality for the initial investigation of the liver worldwide. Normally, the liver can be detected satisfactorily using US except some parts of the subphrenic region [4,5]. Previous studies have found that a tumor located in the subphrenic region is not easy to be detected and it may lead to missed diagnosis [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Normally, the liver can be detected satisfactorily using US except some parts of the subphrenic region [4,5]. Previous studies have found that a tumor located in the subphrenic region is not easy to be detected and it may lead to missed diagnosis [4,5]. Having realized this, US operators always scan the subphrenic region of the liver to avoid the missing detection of focal lesions in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…However, because of the limitation of B-mode US in detecting very early and small HCCs with poor conspicuity, B-mode USguided RFA might result in missed targeting or incomplete ablation (6). The detection rate of small HCCs not greater than 3 cm in diameter was only about 70% with sonography (6,8).…”
Section: Discussionmentioning
confidence: 99%
“…However, because of the limitation of B-mode US in detecting very early and small HCCs with poor conspicuity, B-mode USguided RFA might result in missed targeting or incomplete ablation (6). The detection rate of small HCCs not greater than 3 cm in diameter was only about 70% with sonography (6,8). Although advanced imaging techniques including liver dynamic CT and MRI made it possible to overcome this limitation of sonography and to detect very early HCCs, the treatment for these very small HCCs using US guidance is still challenging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation